Review paperPercutaneous coronary intervention in treatment of multivessel coronary artery disease in patients with non-ST-segment elevation acute coronary syndrome - Gąsior, Paweł; Desperak, Piotr; Gierlaszyńska, Karolina; Hawranek, Michał; Gierlotka, Marek; Gąsior, Mariusz; Poloński, Lech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Among patients with non-ST-elevated acute coronary syndromes (NSTE-ACS) the estimated percentage of single vessel coronary artery disease (SV-CAD) observed during coronarography is about 20-40%, while multivessel coronary artery disease (MV-CAD) is found in about 40-60%. Further treatment in patients with both SV CAD and MV CAD is usually culprit vessel percutaneous coronary intervention (CV-PCI). Nevertheless, in the group of patients with MV-CAD there is still a problematic decision whether the non-infarct related arteries (non-IRA) should be treated with PCI. According to the European Society of Cardiology (ESC) guidelines on myocardial revascularization this decision should be based on the overall clinical and angiographic status of the patient; simultaneously they suggest performing ad hoc CV-PCI. The decision of performing intervention in the rest of the narrowed coronary arteries should be made after consultation with the heart team or according to the protocols adopted in the specific clinic. Furthermore, there is a question of whether the procedure should be performed immediately after culprit vessel revascularization or it should be postponed until the patient is stabilized. Due to the lack of specific recommendations we decided to perform an analysis of existing studies which compared culprit versus multivessel revascularization in patients with MV-CAD and non-ST-elevated acute coronary syndromes.